1999
DOI: 10.1097/00007435-199904000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Douching: Association With Lower Genital Tract Infections in African Pregnant Women

Abstract: The study confirms the widespread practice of douching in African pregnant women. The harmful effects of antiseptics need to be substantiated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 24 publications
3
45
1
Order By: Relevance
“…The 85.5% prevalence of douching found in this study was higher than the 70% reported in Egypt [31], the 58.5% reported among African American women in child-bearing age [32], close to the 90% documented in a South African study [33] but lower than the 97% reported in Cote d'Ivoire (La Ruche et al 1999). Vaginal douching appears to be common especially among Black women of African descent in general, by a third of women in the USA [34,35] as well as in a large proportion of women in Turkey [8].…”
Section: Discussioncontrasting
confidence: 46%
“…The 85.5% prevalence of douching found in this study was higher than the 70% reported in Egypt [31], the 58.5% reported among African American women in child-bearing age [32], close to the 90% documented in a South African study [33] but lower than the 97% reported in Cote d'Ivoire (La Ruche et al 1999). Vaginal douching appears to be common especially among Black women of African descent in general, by a third of women in the USA [34,35] as well as in a large proportion of women in Turkey [8].…”
Section: Discussioncontrasting
confidence: 46%
“…Recent clinical studies suggested that women who frequently douche are associated with an increased risk of pelvic inflammatory disease, 7,8 BV, 9-11 chlamydia, 12 and other sexually transmitted infections, including HIV, [13][14][15] miscarriages, 16 premature birth of low birth-weight infants, 17 ectopic pregnancy, [18][19] and cervical cancer. 20 Nonetheless, data 21,22 that support douching exist.…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical studies suggest a possible association between douching and various health risks in women. These include pelvic inflammatory disease, 7,8 bacterial vaginosis (BV), [9][10][11] chlamydia, 12 and other sexually transmitted infections including HIV, [13][14][15] miscarriages, 16 premature birth of low birth-weight infants, 17 ectopic pregnancy, 18,19 and cervical cancer. 20 Although most published data argue against douching, [7][8][9][10][11][12][13][14][15][16][17][18][19][20] two studies indicated that douching might be medically beneficial.…”
mentioning
confidence: 99%
“…There are only a few studies that show positive effects of vaginal douche over health. Two studies conducted in Africa found evidences that it reduces incidents of HIV and HPV (6,7) . Since these studies were conducted on groups of high risk for sexually transmitted diseases, the hypothesis that they come up to is questionable.…”
Section: Introductionmentioning
confidence: 99%